2021
DOI: 10.1007/s15010-021-01624-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical features and outcomes in COVID-19 and influenza pneumonia patients requiring intensive care unit admission

Abstract: Background Little is known in distinguishing clinical features and outcomes between coronavirus disease-19 (COVID-19) and influenza (FLU). Materials/methods Retrospective, single-centre study including patients with COVID-19 or FLU pneumonia admitted to the Intensive care Unit (ICU) of Policlinico Umberto I (Rome). Aims were: (1) to assess clinical features and differences of patients with COVID-19 and FLU, (2) to identify clinical and/or laboratory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 50 publications
4
19
0
1
Order By: Relevance
“…Our ndings con rm current evidence showing higher mortality and morbidity in SARS-CoV-2 compared to seasonal in uenza [17][18][19][20][21][22] . We have previously shown that elevated PAPsys, most probably due to elevated pulmonary vascular resistance, caused by alveolar and vascular damage, leads to RV-distress in COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…Our ndings con rm current evidence showing higher mortality and morbidity in SARS-CoV-2 compared to seasonal in uenza [17][18][19][20][21][22] . We have previously shown that elevated PAPsys, most probably due to elevated pulmonary vascular resistance, caused by alveolar and vascular damage, leads to RV-distress in COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…[ 23 ]; [ 24 ]; [ 25 ]; [ 26 ]; [ 27 ]; [ 28 ]; [ 29 ]; [ 30 ]; [ 31 ]; [ 32 ]; [ 33 ]; [ 34 ]; [ 35 ]; [ 36 ]; [ 37 ]; [ 38 ]; [ 39 ]; [ 40 ]; [ 41 ]; [ 42 ]; [ 43 ]; [ 44 ]; [ 45 ]; [ 46 ]; [ 47 ]; [ 48 ]; [ 49 ]; [ 50 ]; [ 51 ]; [ 52 ]; [ 53 ]; [ 54 ]; [ 55 ]; [ 56 ]; [ 57 ]; [ 58 ]; [ 59 ]; [ 60 ]; [ 61 ]; [ 62 ]; [ 63 ]; [ 64 ]; [ 65 ]; [ 66 ]; [ 67 ]; [ 68 ]; [ 69 ].…”
Section: Uncited Referencesunclassified
“…The maps on the right show the pooled CAPA incidence per country in studies with observational data. Only studies with exact information on the countries where patients were recruited were included in this figure [2,9,15,16,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][35][36][37][38]40,41,[43][44][45][47][48][49][51][52][53][54][55][56][57][58][59]. CAPA incidence is calculated per study for the combination of proven, probable, putative and possible CAPA cases.…”
Section: Incidencementioning
confidence: 99%